2021
DOI: 10.1088/1367-2630/abfa61
|View full text |Cite
|
Sign up to set email alerts
|

Jerky active matter: a phase field crystal model with translational and orientational memory

Abstract: Most field theories for active matter neglect effects of memory and inertia. However, recent experiments have found inertial delay to be important for the motion of self-propelled particles. A major challenge in the theoretical description of these effects, which makes the application of standard methods very difficult, is the fact that orientable particles have both translational and orientational degrees of freedom which do not necessarily relax on the same time scale. In this work, we derive the general mat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 114 publications
0
20
0
Order By: Relevance
“…Moreover, one could extend the derivation by incorporating also the nematic order parameter (as done in previous derivations for passive models [80][81][82][83]), particle inertia (as done for a singlespecies model in Refs. [87,88]), or by considering a mixture of two different active species. After the ≈ sign in Eq.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, one could extend the derivation by incorporating also the nematic order parameter (as done in previous derivations for passive models [80][81][82][83]), particle inertia (as done for a singlespecies model in Refs. [87,88]), or by considering a mixture of two different active species. After the ≈ sign in Eq.…”
Section: Discussionmentioning
confidence: 99%
“…The active PFC model, an extension of the PFC model to active matter which was proposed and derived from DDFT in Refs. [26,84], has also been extended, allowing one to describe systems on curved surfaces [85], self-spinning particles [86], particles with inertia [87,88], particles with nonreciprocal interactions [89], and mixtures of active and passive particles [12,89] -an extension suggested already in the first article on active PFC models [26]. Further investigations of active PFC models can be found in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover different combinations of friction and memory kernel as well as colored noise can be considered for future work [96][97][98][99][100], for instance, Mittag-Leffler noise [101,102] or power-law memory [103,104]. Finally the collective behavior of many interacting active particles in a viscoelastic medium [105][106][107][108][109][110][111] needs to be explored more and will be an important area of future research.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent experiments [21][22][23] have found that the inertia of active particles is important in a variety of contexts. Moreover, theoretical and experimental studies have found a number of remarkable effects associated with inertial active matter [24], ranging from self-sustained temperature gradients [25] through restored equilibrium crystallization [26] to damping-dependent phase boundaries [27].…”
Section: Introductionmentioning
confidence: 99%
“…Field theories for inertial active matter have been derived in Refs. [27,33,34] as extensions of the active phase field crystal (PFC) model [35][36][37][38]. Active PFC models can be derived as an approximation of dynamical density functional theory (DDFT) [39], and have two disadvantages compared to AMB+.…”
Section: Introductionmentioning
confidence: 99%